Photocatalytic performance of coupled semiconductor ZnO–CuO nanocomposite coating prepared by a facile brass anodization process. (15th November 2021) - Nami, M.; Sheibani, S.; Rashchi, F.
Abstract: Coupled semiconductor metallic oxides have been largely taken into consideration due to the photocatalytic application. In this work, ZnO–CuO coating nanocomposite was fabricated by simple anodic oxidation of alpha brass at different anodizing times. The crystalline structure of hexagonal ZnO and monoclinic CuO phases were demonstrated by X-ray diffraction (XRD). Field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) observation indicated the heterostructure formation of ZnO flower-like and CuO patches-like after 30 min anodizing. Brunauer-Emmett-Teller (BET) method was conducted for specific surface area measurement of the samples. Cyclic voltammetry (CV) and Pourbiax diagram indicated that the brass oxidation process starts with the formation of ZnO followed by CuO formation. Diffuse reflectance spectroscopy (DRS) demonstrated that the band gap energy of the ZnO–CuO nanocomposite narrowed by raising anodizing time owing to the formation of the Cu(3d) energy state near the Zn (3d) valence band. Photoluminescence (PL) spectra revealed that the lifetime of the photo-excited electron-hole increased by the effective combination between CuO and ZnO in anodized brass after 30 min. The photocatalytic performance of ZnO–CuO nanocomposites with different anodization times was estimated by the degradation of 2 mg/L methylene blue (MB) and colorless phenol solution under visible light irradiation. After 30 min, the anodized brass with an estimated 3 eV band gap energy exhibited 54 and 49% degradation of MB and phenol, respectively, after 300 min, which was the highest efficiency among all the samples. Also, the highest photo-degradation was obtained at 8 mm 2 /mL of surface area to volume of dye solution. Recyclability results showed only a 5% drop-in photocatalytic activity after three cycles. Finally, the photo-degradation mechanism was proposed based on the role of holes and hydroxyl radicals, using various scavengers.